Day and Night. Activities by and for the Children from El Refugio in Ancient Neighbourhoods of the Historic Centre of Puebla - Hernández Sánchez, Adriana; De La Torre Sánchez, Christian Enrique (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2023)
The purpose of the following investigation is to understand how children from the old historic district El Refugio (or Barrio del Refugio) of the city of Puebla (Mexico) live in public spaces and what their days and nights look like. It is extremely important to understand the reasons for their appropriation of various places in the city because it allows one to explore the conditions in which they manifest autonomous attitudes. This article is therefore not only about customs and culture, but also about everyday relationships with the environment. Children are also involved in the activities of the group Re Genera Espacio (RGE) and the team of Benemérita Universidad Autónoma de Puebla (BUAP) in the development of all kinds of educational, artistic, and social activities. Among the most important results obtained is the observation that safety conditions are created by children in independent groups which move to other neighbourhoods (“barrios”), such as San Antonio and Santa Anita. Children make the street their space because they have important knowledge of the area.